Achalasia: Dilation, Injection or Surgery?. (1st May 2000) - Peracchia, Alberto; Bonavina, Luigi
Abstract : Achalasia results from irreversible alterations of the esophageal myenteric plexus. The target of treatment in this setting is to reduce lower esophageal sphincter resistance to passage of the bolus. Definitive treatment of the disease requires pneumatic dilation or Heller myotomy. Although no controlled studies comparing modern endoscopic and surgical techniques are available, laparoscopic surgery is emerging as the initial intervention of choice.